2019
DOI: 10.1371/journal.pntd.0007126
|View full text |Cite
|
Sign up to set email alerts
|

Triple oral beta-lactam containing therapy for Buruli ulcer treatment shortening

Abstract: The potential use of clinically approved beta-lactams for Buruli ulcer (BU) treatment was investigated with representative classes analyzed in vitro for activity against Mycobacterium ulcerans. Beta-lactams tested were effective alone and displayed a strong synergistic profile in combination with antibiotics currently used to treat BU, i.e. rifampicin and clarithromycin; this activity was further potentiated in the presence of the beta-lactamase inhibitor clavulanate. In addition, quadruple combinations of rif… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
2

Relationship

3
6

Authors

Journals

citations
Cited by 15 publications
(26 citation statements)
references
References 62 publications
4
22
0
Order By: Relevance
“…Here, we evaluated the emergence of resistance to a combination of a β-lactam (CEF) and rifampicin (RIF). These two drugs are synergistic in B. subtilis , as shown also for other bacteria ( 56 59 ). We used in vitro evolution followed by whole-genome sequencing to identify mutations that enable growth in the presence of this dual selection.…”
Section: Discussionsupporting
confidence: 58%
“…Here, we evaluated the emergence of resistance to a combination of a β-lactam (CEF) and rifampicin (RIF). These two drugs are synergistic in B. subtilis , as shown also for other bacteria ( 56 59 ). We used in vitro evolution followed by whole-genome sequencing to identify mutations that enable growth in the presence of this dual selection.…”
Section: Discussionsupporting
confidence: 58%
“…Here, we evaluated the emergence of resistance to a combination of a β-lactam (CEF) and rifampicin (RIF). These two drugs are synergistic in B. subtilis, as shown also for other bacteria (53)(54)(55)(56). We used in vitro evolution followed by whole-genome sequencing to identify mutations that enable growth in the presence of this dual selection.…”
Section: Discussionmentioning
confidence: 94%
“…Interestingly, zidovudine displayed strong synergy with both drugs. We thus aimed to characterize whether the addition of zidovudine to the fosfomycin/colistin combination could further potentiate the synergistic interaction, as previously described (24,30,31). The triple combination was highly active showing bactericidal activity to the limit of detection in 4 out of 8 strains tested.…”
Section: Resultsmentioning
confidence: 99%
“…Given that our studies demonstrated that zidovudine-based combinations are more potent than currently clinically used for the treatment of infections caused by MDR/XDR K. pneumoniae strains, we performed TKA to characterize the potential impact of zidovudine in a triple combination with fosfomycin and colistin. In mycobacteria, triple combinations perform better than the sum of the pairwise combinations (24,30,31); however, this was not the case and the triple combination added little value to fosfomycin/colistin ( Figure 2 ).…”
Section: Discussionmentioning
confidence: 99%